Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12967-023-04525-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide mendelian randomization study implicates therapeutic targets in common cancers

Feihong Ren,
Qiubai Jin,
Tongtong Liu
et al.

Abstract: Background The interest in targeted cancer therapies has been growing rapidly. While numerous cancer biomarkers and targeted treatment strategies have been developed and employed, there are still significant limitations and challenges in the early diagnosis and targeted treatment of cancers. Accordingly, there is an urgent need to identify novel targets and develop new targeted drugs. Methods The study was conducted using combined cis-Mendelian ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Despite, the application of MR in identifying plasma proteins as drug targets in breast cancer is still sporadic. For instance, one study performed MR analysis on a single cohort of 732 plasma proteins, where GDI2 and CTSF were identified as potential targets for breast cancer ( Ren et al, 2023 ), aligning with our research. However, it is important to note that this study also focused on pan-cancer research and lacked association analysis.…”
Section: Discussionsupporting
confidence: 75%
“…Despite, the application of MR in identifying plasma proteins as drug targets in breast cancer is still sporadic. For instance, one study performed MR analysis on a single cohort of 732 plasma proteins, where GDI2 and CTSF were identified as potential targets for breast cancer ( Ren et al, 2023 ), aligning with our research. However, it is important to note that this study also focused on pan-cancer research and lacked association analysis.…”
Section: Discussionsupporting
confidence: 75%
“…ALAD is significantly decreased in breast and hepatocellular carcinoma, and its reduced expression is correlated with an unfavorable prognosis in patients [ 67 , 68 ]. Yh Yang et al also found a significant association between ICAM5 and LUAD risk, suggesting its potential as a target for lung cancer [ 69 , 70 ]. MDGA2 is a tumor suppressor in gastric carcinogenesis, and its hypermethylation is an independent prognostic factor in gastric cancer patients [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary zeniths in research, namely cancer immunotherapy, which includes checkpoint inhibitors and adoptive cellular therapy, strategize to recalibrate the immune system for the identification and eradication of neoplastic cells. A luminary target within this therapeutic domain for addressing prostate carcinoma is the PDIA3 protein [ 26 , 27 ]. The realms of biotechnology and microbial studies ceaselessly advance in devising innovative curatives for an array of carcinomas, CRC included, proffering a glimmer of solace for those besieged by this scourge.…”
Section: Discussionmentioning
confidence: 99%